HUBUNGAN ANTARA INTENSITAS KEBISINGAN MUSIK DISKOTIK DAN MASA KERJA DENGAN FUNGSI PENDENGARAN KARYAWAN DISKOTIK DI PONTIANAK TAHUN 2013 - ., Sandy Tambunan (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Hearing loss is the most common sensoric impairmentfound in human population, affects more than 250 million of world society.In 2002 prevalence of hearing loss in Indonesia was 4,2% of population orabout 9,3 million people. One of the causes of hearing loss is exposure tointensity of noise. Discotheque music noise exceed noise threshold limitvalue (85 dBA), so that discotheque employees are at risk of havinghearing loss. Objective. The aim of this study was to assess the relationbetween intensity of discotheque music noise and working period withhearing function among discotheque employees in Pontianak in 2013.Method. This research was an analytic study with cross sectional design.The data was obtained from Biztro Discotheque of Kapuas Palace Hoteland MGM Discotheque of Garuda Hotel. Twenty three employees wereincluded in this research. Noise intensity was measured by sound levelmeter, anamnesis was taken from the employees, and hearing functionwas assessed by audiometer. Result. The rate of highest noise intensitymeasured was 101,3 dBA. Sensorineural hearing loss was found in 4employees (17,4%). Fisher test showed no relation between noiseintensity or working period with hearing function (p = 1 and p = 0,26,respectively). Conclusion. There was no significant relation betweenintensity of discotheque music noise and working period with hearingfunction among discotheque employees in Pontianak in 2013.Keywords: noise intensity, working period, hearing function, discotheque Notes 1) Medical School, Faculty of Medicine, Tanjungpura University,Pontianak, West Kalimantan. 2) Department of Public Health, Medical School, Faculty of Medicine,Tanjungpura University, Pontianak, West Kalimantan. 3) Department of Physiology, Medical School, Faculty of Medicine,Tanjungpura University, Pontianak, West Kalimantan.